Interview of Thomas Gray by Raimund E. Goerler - Gray, Thomas, 1919- (Byrd Polar Research Center Archival Program, 2006)
Aarruiz, Alberto, Argentine meteorologist, pp. 7, 18 Alt, John, French meteorologist, pp. 7, 17 Astapenko, Paul, Russian meteorologist, pp. 7, 16-17 Cochran, Henry, American meteorologist, pp. 7, 23 Crary, Albert, explorer, pp. 19, 23 Gould, Larry, Head official for the Antarctic program in 1957-58, p. 5 Morley, Keith, Australian meteorologist, pp. 7, 18, Rao, P. Krisna , meteorologist, p. 28 Ropar, Nick, American meteorologist, p. 7 Wexler, Henry, prominent meteorologist, pp. 3-6, 25 The media can be accessed at the links below. Audio Part 1: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Thomas_Gray_1.mp3 Audio Part 2: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Thomas_Gray_2.mp3 After a year of graduate study in meteorology at the University of Chicago, Thomas Gray was hired in 1941 by the U.S. Weather Bureau in Washington, D.C. He advanced rapidly and soon became the senior analyst and assistant forecaster in the Extended Forecast department. In 1957, upon the recommendation of Dr. Harry Wexler and others, Gray was selected to be head of the Antarctic Weather Center at the Little America base. He served from November, 1957 until January, 1959. The Center was a truly international operation. Meteorologists worked there from many nations who participated in the International Geophysical Year (IGY), including South Africa, Chile, Argentina, Australia, France, and the USSR. All of the staff worked under Gray’s direction. The Weather Center provided daily weather information to all stations in the Antarctic, and occasionally for particular air flights. Most of the men also found time to do work on individual research projects. Gray’s own role was primarily that of a facilitator to other researchers. The weather central operated daily from 5:00 A.M. until 2:00 A.M the next day. Gray’s American assistants were Nick Ropar and Henry Cockran, plus several others from different nations, all of whom were required to speak English. Communications were primitive at the time and so weather ...